Faktor Kepuasan Kerja dan Motivasi Sebagai Dampak dari Kinerja Pegawai. (Studi Pada Aparatur Sipil Negara dan Non Aparatur Sipil Negara pada Kantor Instansi Pemerintah Kabupaten Luwu). - Jumarpati, Jumarpati; Dewi, Siti Kumala (YUME : Journal of Management, 2024)
Organizational commitment is one of the keys to determining the success or failure of an organization in achieving its goals. Employees who are committed to the organization usually show a work attitude that is full of attention to their duties. They are very responsible for carrying out their duties and are very loyal to government agencies. In government agencies, one of the symptoms of a lack of stability in government organizations is low employee performance. Low employee performance can result in obstacles to achieving organizational goals. This research aimed to analyze the influence of the work environment on employee performance in the technical implementation unit of the South Sulawesi Provincial Forestry Service in Tana Toraja region. This research was conducted at the South Sulawesi Provincial Forestry Service Office, Tana Toraja Region. The population in this research was all employees at the Technical Implementation Unit office of the South Sulawesi Provincial Forestry Service in the Tana Toraja region from January 2022 to June 2022, totaling 105 peoples. The sample in this study was 105 people. The data analysis was descriptive analysis and inferential analysis. This research used Structural Equation Modeling Based Variance (VB-SEM) analysis with the help of Smart PLS 3.3 software. The results of the research show that the results of the statistical T analysis obtained a calculated t value = 3.989> t table = 1.893 with a P value of 0.000 or smaller than the cut off value of 0.05. This means that the organizational commitment variable (X1) has a significant effect on employee performance (Y). The results of the T statistical analysis on variable This means that the work environment variable (X2) has a significant effect on employee performance (Y).Keywords: Employee Performance, Organizational Commitment, Work Environment